Youth 2020: The position of young people in Slovenia (University of Maribor Press, 2021)
After ten years, we are again facing a survey on the position of young people in Slovenian society Mladina 2020. As this is a national survey on the young generation between 15-29 years, its informative value is for the client (Office of the Republic of Slovenia for Youth) society as a whole is of paramount importance. Our goal is primarily to realize the basic purpose of the research, which is to provide support in the Office in the next few years with the help of Youth 2020 with evidence of supported formulation of public policies in the field of youth. Along with the research, the contractors also prepared recommendations that can serve as a starting point for the design of measures. The latter should provide young people with better conditions for the transition to adulthood, and adults a peaceful maturity, aware that the young generation is empowered and well prepared to face all life circumstances. Is that true? So what is our youth like on the threshold of the 21st century?